Autonomous tracking of honey bee behaviors over long-term periods with cooperating robots - Ulrich, Jiří; Stefanec, Martin; Rekabi-Bana, Fatemeh; Fedotoff, Laurenz Alexander; Rouček, Tomáš; Gündeğer, Bilal Yağız; Saadat, Mahmood; Blaha, Jan; Janota, Jiří; Hofstadler, Daniel Nicolas; Žampachů, Kristina; Keyvan, Erhan Ege; et al. (Science robotics, 2024)
Digital and mechatronic methods, paired with artificial intelligence and machine learning, are transformative technologies in behavioral science and biology. The central element of the most important pollinator species-honey bees-is the colony's queen. Because honey bee self-regulation is complex and studying queens in their natural colony context is difficult, the behavioral strategies of these organisms have not been widely studied. We created an autonomous robotic observation and behavioral analysis system aimed at continuous observation of the queen and her interactions with worker bees and comb cells, generating behavioral datasets of exceptional length and quality. Key behavioral metrics of the queen and her social embedding within the colony were gathered using our robotic system. Data were collected continuously for 24 hours a day over a period of 30 days, demonstrating our system's capability to extract key behavioral metrics at microscopic, mesoscopic, and macroscopic system levels. Additionally, interactions among the queen, worker bees, and brood were observed and quantified. Long-term continuous observations performed by the robot yielded large amounts of high-definition video data that are beyond the observation capabilities of humans or stationary cameras. Our robotic system can enable a deeper understanding of the innermost mechanisms of honey bees' swarm-intelligent self-regulation. Moreover, it offers the possibility to study other social insect colonies, biocoenoses, and ecosystems in an automated manner. Social insects are keystone species in all terrestrial ecosystems; thus, developing a better understanding of their behaviors will be invaluable for the protection and even the restoration of our fragile ecosystems globally.
Keywords: Equipment Design; Animals; Female; ženské pohlaví; Robotics; strojové učení; chování zvířat; umělá inteligence; robotika; Video Recording; Machine Learning; Bees; Behavior, Animal; včely; Social Behavior; audiovizuální záznam; zvířata; design vybavení; sociální chování; Artificial Intelligence